(untitled) (Modern education and development, 2025)
This article explores the challenges faced by primary school teachers in fostering effective interaction with their pupils during lessons. It examines common behavioral, communicative, and pedagogical obstacles that hinder productive classroom interaction. Additionally, it investigates the psychological and developmental characteristics of young learners that influence their classroom engagement. Practical solutions and strategies are proposed to enhance teacher-student interaction, grounded in contemporary educational theories and empirical findings. The study aims to support educators in creating more inclusive, communicative, and student-centered learning environments.